Manajemen Kemitraan Perguruan Tinggi Vokasi dengan DUDI untuk Meningkatkan Keterserapan Lulusan dalam Dunia Kerja di Kabupaten Aceh Barat - Riza Hasan; Rahmad Nuthihar; Hanif Hanif; Juanda Juanda (Kolaborasi : Jurnal Administrasi Publik, 2023)
The purpose of this study was to determine (1) the partnership management of the West Aceh State Community Academy (AKN) with the Business and Industrial World (DUDI) the level of absorption of graduates in the world of work; (2) efforts that can be made to increase the absorption of graduates in the world of work. This research uses a qualitative approach with a descriptive type. Data collection by way of observation, documentation, and interviews while data analysis using interactive analysis. The results of this study are (1) partnership management between West Aceh AKN and DUDI to increase the absorption of graduates in the world of work. This is based on the findings of problems in each aspect of the West Aceh AKN partnership management; (2) efforts that can be made to increase the absorption of graduates in the world of work are (a) involving DUDI in the preparation of the curriculum; (b) involve DUDI as an instructor/guest lecturer; (c) involve DUDI to provide knowledge competency tests after students carry out field work practice programs.